2020
DOI: 10.1007/s41669-020-00215-w
|View full text |Cite
|
Sign up to set email alerts
|

Fall/Fracture-Related Healthcare Costs and Their Association with Cumulative Anticholinergic Burden in People with Overactive Bladder

Abstract: Background Falls/fractures are major causes of morbidity and mortality among older adults and the resulting health consequences generate a substantial economic burden. Risk factors are numerous and include overactive bladder (OAB) and anticholinergic use. Objectives We aimed to estimate the impact of falls/fractures on all-cause healthcare resource utilization and costs, according to levels of cumulative anticholinergic burden, among individuals with OAB. Methods Among a US cohort of adults with OAB (identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…Despite differences in study populations, these findings are largely in line with previous observations that healthcare resource utilization among community-dwelling adults with OAB increased with higher levels of anticholinergic burden [36]. Lozano-Ortega et al found that among commercially insured OAB patients in the US, approximately 65% of individuals had some level of anticholinergic burden [36]. Significantly greater healthcare resource utilization was observed among those with any level of anticholinergic burden (low, moderate, or high) versus those with no burden.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite differences in study populations, these findings are largely in line with previous observations that healthcare resource utilization among community-dwelling adults with OAB increased with higher levels of anticholinergic burden [36]. Lozano-Ortega et al found that among commercially insured OAB patients in the US, approximately 65% of individuals had some level of anticholinergic burden [36]. Significantly greater healthcare resource utilization was observed among those with any level of anticholinergic burden (low, moderate, or high) versus those with no burden.…”
Section: Discussionsupporting
confidence: 88%
“…Significantly greater healthcare resource utilization was observed among those with any level of anticholinergic burden (low, moderate, or high) versus those with no burden. Indeed, the relationships reported by Lozano-Ortega et al between level of anticholinergic burden and healthcare costs were more consistently linear than the relationships in the present study, where costs and utilization were at times observed to peak with moderate levels of burden [36]. However, although there was variability in healthcare costs across anticholinergic burden groups in the present study, healthcare costs were generally higher among those with higher anticholinergic burden.…”
Section: Discussioncontrasting
confidence: 55%
“…Demographics were observed during year 1 and included age category, sex, census region, nursing home category, and calendar year. Medical conditions included those associated with a higher risk of falls and fractures from Szabo et al [19] (e.g., Parkinson's disease, dementia, hypertension, and diabetes), Elixhauser comorbidities [14,24], and conditions indicated for treatment with an anticholinergic medication (Fall/fracture-related diagnostic codes: Predictive margins and average marginal effects on the original scale (i.e., probability, dollars) and their 95% CIs as well as relative risks were calculated from each regression model. Estimated standard errors were adjusted to be robust to heteroskedasticity of unknown form and for multiple yearly observations per person.…”
Section: Statistical Analysis: Associations Between Poly-ach Status and Outcomesmentioning
confidence: 99%
“…One study found that among commercially insured patients with OAB in the USA, approximately 65% had some level of anticholinergic burden. Furthermore, healthcare resource utilization and costs directly increased with a higher level of anticholinergic burden [ 14 ]. Likewise, a study of 3344 community-dwelling older adults found that increasing levels of anticholinergic burden were also associated with higher costs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while this study did not attempt to quantify the effect of anticholinergic burden on the outcomes herein, it should be noted that both OAB and depression are frequently treated with anticholinergics [ 25 , 26 ]. Studies have linked long-term anticholinergic use with dementia [ 27 ] and falls and fractures [ 28 ] and have noted concomitant increases in costs and resource use [ 29 ]. As such, it is possible that the increase in costs identified here could, in some measure, be the result of anticholinergic burden, particularly if patients are using drugs of that class to treat both conditions.…”
Section: Discussionmentioning
confidence: 99%